EVALUATION TO DROUGHT-RESISTANT TRAIT OF SOYBEAN VARIETIES BY USINGANATOMICAL, MORPHOLOGICAL AND PHYSIOLOGICAL CHARACTERISTICS (Experimental biology, 2016)
Soybean plants use variousprocesses to cope with the drought stress and these processesregulates by a combination of factors. Plant stability to drought is very complex and involves interaction between various molecular, biochemical and physiological processes. These appliances include highly water absorbing roots, the development of more long taproot, which helps to reach the lower layers of soil, reducing evaporation from the surface organs by formation of smaller leaves, high efficiency of transpiration, adjustable partial closing of the stomata, the presence of hairs that protect from the list overheating and intense solar radiation. Soybeansvarieties admitted to using in Kazakhstan and advanced breeding lines of the Kazakh Research Institute of Agriculture and crop production were studiedby anatomical, morphological and physiological characteristics. These researches helpto select and allocatedrought-tolerant soybean varieties. The evaluation selected varieties or lines with high downy, a large number of stomata (Selecta 302,Bucuria, Voevodzhanka) and varieties with a high index of resistance to osmotic stress (Zen, Terek, Cheremosh).
Keywords: soybean; drought-tolerant; anatomical and morphological characteristics; physiological symptoms; kseromorfizm.